In Search of Precision in Absorptive Capacity Research: A Synthesis of the Literature and Consolidation of Findings. (July 2018) - Song, Yue; Gnyawali, Devi R.; Srivastava, Manish K.; Asgari, Elham
This paper addresses two fundamental problems in the absorptive capacity (AC) literature: conceptual ambiguity on what AC is and a lack of synthesized empirical findings showing how AC matters for firm outcomes. We take a two-pronged approach to address these problems: (1) conceptual distillation of the literature to discern the core AC dimensions, outcomes, and contingent external knowledge conditions and (2) meta-analysis of the empirical literature to synthesize the findings. For conceptual distillation, we identify three dimensions of AC: absorptive effort (i.e., the knowledge-building investments made by a firm), absorptive knowledge base (i.e., the current knowledge stock of a firm), and absorptive process (i.e., a firm's internal procedures and practices related to knowledge diffusion). We develop these dimensions by explicating their theoretical roots, functions, mechanisms, and corresponding measures. Leveraging the conceptual distillation, we conduct meta-analyses of the empirical literature and synthesize key findings. We find that AC has a significant positive effect on firm outcomes and that the most commonly used dimension, absorptive effort, has the lowest mean effect size. We also find that knowledge acquisition and innovation generation fully mediate the effect of absorptive knowledge base but partially mediate the effects of absorptive effort and absorptive process on firm performance. Furthermore, AC's effects on firm outcomes vary across external knowledge contingencies. Overall, this paper provides a strong theoretical and empirical basis to advance a dimensional approach in AC research and thereby facilitates a more rigorous research necessary for cumulative knowledge development on this important topic.